A Literature Review on the GDPR, COVID-19 and the Ethical Considerations of Data Protection During a Time of Crisis - Christofidou, Maria; Lea, Nathan; Coorevits, Pascal (Yearbook of Medical Informatics, 2021)
Objective: This survey article presents a literature review of relevant publications aiming to explore whether the EU's General Data Protection Regulation (GDPR) has held true during a time of crisis and the implications that arose during the COVID-19 outbreak.Method and Results: Based on the approach taken and the screening of the relevant articles, the results focus on three themes: a critique on GDPR; the ethics surrounding the use of digital health technologies, namely in the form of mobile applications; and the possibility of cross border transfers of said data outside of Europe. Within this context, the article reviews the arising themes, considers the use of data through mobile health applications, and discusses whether data protection may require a revision when balancing societal and personal interests.Conclusions: In summary, although it is clear that the GDPR has been applied through a mixed and complex experience with data handling during the pandemic, the COVID-19 pandemic has indeed shown that it was a test the GDPR was designed and prepared to undertake. The article suggests that further review and research is needed to first ensure that an understanding of the state of the art in data protection during the pandemic is maintained and second to subsequently explore and carefully create a specific framework for the ethical considerations involved. The paper echoes the literature reviewed and calls for the creation of a unified and harmonised network or database to enable the secure data sharing across borders.
Keywords: COVID-19; data protection; ethics; privacy; public health